PENGARUH TINGKAT PENDIDIKAN DAN JENIS PEKERJAAN TERHADAP PRODUKTIVITAS DAN PENDAPATAN KELUARGA MISKIN KECAMATAN NEGARA JEMBRANA - Gautama, Nyoman Shaka; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
The number of poor families is almost in line with the development of the population. This shows that the development of the population followed by an increase in the number of poor families, this is due to the influence that causes the family classified as poor one of which is low income. The purpose of this study was to analyze the effect of education level and type of work on the productivity, income of poor families in Jembrana district sub-districts. The data used are primary and secondary data. Data collection methods used in this study were observation, structured interviews and in-depth interviews. Using sample of 89 respondents with the analysis technique used is a quantitative analysis technique. The results of this study are the level of education and type of work have a positive and significant effect on the productivity of poor families. The level of education and type of work have a positive and significant effect on the income of poor families. The level of education and type of work have an indirect effect on the income of poor families through productivity in the state sub-district of Jembrana district.   Keywords: income, productivity, education, type of work, poor families